Peningkatan Omset Usaha Keripik Nanas Khas Pekanbaru Melalui Pembaharuan Desain Packaging Dan Pengembangan Pemasaran Produk - Wan laura Hardilawati; Arista Tri Astuti; Alex Candra; Kintan Syafwa Prastika; Muhammad Abrar Al-azhar (LPPM UMRI, 2021)
This research aims to outline the results of research on the increasing turnover of the typical pineapple chips business of pekanbaru through packaging design renewal and product marketing development.This pineapple chips business has excellent potential, so it needs to get special attention from various parties such as from government, private and college as has been done by many universities through community service activities.This research focuses on packaging, design and marketing of pineapple chips products of Ibu's new business located on the outskirts of the city, precisely on Rimbo Panjang street, Pekanbaru.Through this devotional activity, pineapple chip manufacturers can increase knowledge on how to attract consumers by changing packaging to be safer along with a more attractive design display that can become a product identity and market products through e-commerce to increase productivity and sales.